Pengaruh Kompos Limbah Ampas Tebu Terhadap Pertumbuhan dan Hasil Tanaman Cabai Merah (Capsicum annum L.) - Elly Indra Swari; Nerty Soverda; Mahesa Givan Pengestu (Universitas Batanghari, 2022)
The purpose of this study was to study the effect of bagasse compost on the growth and yield of red chili (Capsicum annum L.), and to obtain a dose of bagasse compost that could provide the best growth and yield of red chili. This research was conducted at the Teaching and Research Farm, Faculty of Agriculture, Jambi University, Mendalo Indah Village, Outer Jambi District, Muaro Jambi Regency, Jambi Province. The study was carried out from April to August 2020. The design used was a Randomized Block Design (RAK) consisting of 5 treatment levels, namely: without bagasse compost (p0), 200 g bagasse compost (p1), 300 g (p2) , 400 g (p4), and 500 (p5). The treatment was repeated 5 times, so there were 25 experimental units. Each experiment contained 5 polybags where each polybag contained one plant and 3 as sample plants. From the results of the study, it was found that giving a dose of 500 g of bagasse compost was the best dose that affected the number of branches, number of fruit per plant, and fruit weight per plant.